Green synthesis of copper oxide nanoparticles (cuo nps) using orange (citrus sinensis) peel extract and their photocatalytic performance on rose bengal b dye - Chan, Yi Min (2024)
Copper oxide nanoparticles (CuO NPs) are synthesized through green synthesis, utilizing the natural phytochemicals present in orange (Citrus sinensis) peel as green stabilizing and reducing agents. This synthesis route offers several advantages, including higher sustainability, eco-friendliness, lower cost, reduced generation of toxic chemical waste, and the utilization of a renewable source of stabilizing and reducing agents in the synthesis process. CuO NPs are synthesized using copper (II) nitrate trihydrate and copper (II) acetate monohydrate as precursor salts, along with orange peel extract (OPE) prepared using boiling, soaking, and maceration methods, followed by calcination at 450°C and 500°C for 2 hours. The greensynthesized CuO NPs were characterized by using various analytical tools such as X-ray diffraction (XRD), field emission scanning electron microscopy (FE-SEM), Fourier transform infrared spectroscopy (FTIR), UV-Vis absorption spectroscopy (UV-Vis), and Energy Dispersive X-ray (EDX). The effects of OPE preparation method, calcination temperature, and type of precursor salt on green-synthesized CuO NPs were studied through a comparison of characterization results of CuO NPs synthesized under different conditions (type of OPE, type of precursor salt, and calcination temperature). The optimized synthesis conditions for CuO NPs were determined. The photocatalytic activity of OPE-mediated CuO NPs under the optimized conditions was studied using an aqueous Rose Bengal B (RBB) dye solution under an 18-Watt UV light, monitored with a UV-Vis spectrophotometer. It was observed that 91.29% of RBB dye was degraded in the presence of OPE-mediated CuO NPs under 18-Watt UV light.